A first demonstration and analysis of the biprimary color system for reflective displays. Issue 2 (28th August 2014) - Mukherjee, Sayantika; Smith, Nathan; Goulding, Mark; Topping, Claire; Norman, Sarah; Liu, Qin; Kramer, Laura; Kularatne, Senal; Heikenfeld, Jason
Abstract A new biprimary color system is demonstrated for single‐layer reflective displays, capturing much of the improved color performance of multilayer displays while potentially maintaining single‐layer display advantages in high resolution and faster switching. Electrophoretic pixels were operated with dual‐particle complementary‐colored dispersions such as green/magenta (G/M). Using simple interdigitated three‐electrode architecture, four colored states (KWGM) were achieved with a preliminary contrast ratio of 10 : 1. Furthermore, biprimary ink dispersions were shown to be functional in a more advanced electrokinetic pixel structure. A full‐color biprimary pixel contains three complementary subpixels (G/M, B/Y, R/C), and the requisite electrophoretic ink dispersions were also formulated and spectrally characterized in this work. Lastly, theoretical color space mapping confirms that the biprimary concept provides twice the brightness and twice the color fraction compared with the conventional RGBW subpixel approach, and that the biprimary concept can approach performance close to that of magazine print (Specifications for Web‐Offset Print).